Case Method: Mengoptimalkan Critical Thinking, Creativity Communication Skills dan Collaboratively Mahasiswa Sesuai MBKM di Era Abad 21 - Endah Andayani (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2022)
The implementation of the case method have been carried out intensely by all Lecturers at the Faculty of Economics and Business (FEB) in the last 1 (one) year. The case method as one of the methods in accordance with the Merdeka Learning program at the Merdeka campus (MBKM) has opportunities and contributes to improving Creativity, Critical Thinking, Communication, and Collaboration (4Cs) skills as skills needed in the 21st century era. This study aims to describe implementation of the case method carried out by the lecturer; and analyze the impact of case method learning activities on students perceived by lecturers. This type of research uses qualitative with a case study approach. The Sources of data came from 37 informants, namely all FEB lecturers. The data collection technique using the distribution of a google form-assisted questionnaire which was validated through triangulation; interviews, observations, and data analysis were carried out using descriptive analytical techniques. The results showed that 28 of the 37 lecturers studied had a very good understanding of how to implement the case method in lectures well. The results of the questionnaire analysis also showed that 87% of lecturers stated that case-based learning method was effective in overcoming demotivation in students; anticipating the impact of learning loss as a result of the implementation of online learning that lasts for quite a long time; and inspire students' enthusiasm to master the material more deeply. It is hoped that in future studies, the Faculty will make a policy to require lecturers to use one of the methods according to the MBKM program.